USE OF KB INJECTIONS FOR 3 MONTHS AT THE PUSKESMAS BALOI PERMAI, BATAM CITY - Muhammad Rifki; Rosyadi Aziz Rahmat (Universitas Batam, 2021)
Injectable birth control methods use medroxyprogesterone (a type of progestin) which is injected once or 3 months into the buttocks or upper arm muscles. This is very effective but can interfere with the menstrual cycle. The results of several studies conducted on injection family planning acceptors showed that the factors associated with injection contraceptive use were menstrual disorders 51.25%, 36.25% increase in body weight and an increase in blood pressure. Some of the results of studies conducted on injection contraceptive acceptors showed that factors which is associated with the use of injection contraceptives is the occurrence of menstrual disorders 51.25%, weight gain 36.25% and an increase in blood pressure 3.75% (Eiska, 2007). Method : The research objective was to determine the use of 3-month injection of family planning at the UPT Puskesmas Baloi Permai. The population of this study were mothers who used 3-month injection contraception. Sampling with purposive sampling technique. The number of samples is 98 respondents. Result :The univariate results obtained were more than half of the respondents who used 3-month injection contraception (57.1%). Conclusion : Based on the results of the research that has been carried out, it can be concluded as follows : The conclusion in this study was that 98 respondents obtained the results, namely, respondents who used injection contraceptives for 3 months with categories using as many as 92 people (93.9%